The perils of prediction in the Physical Sciences: Historical and epistemological perspectives: Introduction - Arabatzis, Theodore; Arapostathis, Stathis; Katsaloulis, Iraklis; Tympas, Telis (Neusis, 2025)
This article is an introduction to the special issue of Neusis on the perils of prediction in the physical sciences. It provides a brief overview of some literature on the history and epistemology of prediction and summaries of the papers included in the special issue.